Pembuktian Keterangan Saksi Anak Tanpa Sumpah Menurut KUHAP - Dipta Yoga Pramudita; Bambang Santoso, S.H., M.Hum (Sebelas Maret University, 2017)
The purpose of this study was to determine the child’s evidence witness statements without oath under Article 171 and Article 184 Criminal Procedural Code in proving the case with the threat of force children copulating in Karanganyar District Court. This legal writing including normative law research, using primary and secondary data sources, primary legal materials in the form of Karanganyar District Court's Decision Number 132 / PID.SUS / 2014 / PN.Krg. Source of data used is the Criminal Procedural Code, Act number 23 of 2002 on Child Protection, and other library materials. Data collection techniques used is through secondary data collection, carried out literature studies to collect and collate data related to the problems examined. The data have been obtained after passing the data processing mechanism is then determined the type of analysis, so that the data collected more accountable. Information submitted by the child victims can have the strength of evidence. The victim witness submit the information without an oath in court, under Article 171 and Article 184 Criminal Procedural Code which explains that a child under age may testify without oath, then the information conveyed was appropriate with the Criminal Procedural Code. Keywords: Witness testimony, Child Witness, Without Oath